Capital-Market Liberalization is Certainly no Paragon of Virtues: A Theoretical Review - Chandra, Parag; Chakraborty, Saptorshee Kanto (Indian Journal of Finance, 2014)
The theory of capital market liberalization is based on two central assumptions- convex technologies and concave preference functions faced by agents. Standard models employed by the economists of the International Monetary Fund (which we simply call the Fund) justifiably reveal that more the financial market is globally integrated, the better are the risks dispersed, based on the above mentioned assumptions. So, the Fund's economists deliberately claim that full capital market liberalization helps cross-country smoothing of any adverse shock. However, ironically, the above-mentioned proposition is true when capital flows are counter cyclical. In reality, capital flows pro-cyclically because of the credit market imperfections, giving rise to a natural set of non-convexities. In this paper, we have made a modest attempt to review why capital market liberalization leads to economic instability instead of accelerating economic growth.